The impact of influencer marketing and instagrammers on consumer purchase intentions and brand attitude - Bilro, R. G.; Loureiro, S. M. C.; Rosado-Pinto, F.; Costa, I. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
In the last few years, we have noticed the emergence of influencer marketing (Lanz, Goldenberg, Shapira, & Stahl, 2019; Sokolova & Kefi, 2019), specifically of how some of this arising-stars in the social media spectrum have become sources of advice for other consumers, resulting in opinion leaders for the brands they advocate (Casaló, Flavián, & Ibáñez-Sánchez, 2018). As this trend is expected to continue in the near future, the current research focuses in one of the fastest-growing social media platforms - Instagram - (De Veirman, Cauberghe, & Hudders, 2017; Sheldon, Rauschnabel, Antony, & Car, 2017) to understand how Instagrammers and their posts have an impact on consumer’s purchase decisions for the young-adult audiences. Additionally, this study also aims to understand if this content creation influences consumer’s brand attitude (Faircloth, Capella, & Alford, 2016), that is, in the consumer’s opinion about a product or service of a specific brand.